2017
DOI: 10.2147/ndt.s136774
|View full text |Cite
|
Sign up to set email alerts
|

Reduced prefrontal activation during verbal fluency task in chronic insomnia disorder: a multichannel near-infrared spectroscopy study

Abstract: PurposeDaytime complaints such as memory and attention deficits and failure to accomplish daily tasks are common in insomnia patients. However, objective psychological tests to detect cognitive impairment are equivocal. Neural function associated with cognitive performance may explain the discrepancy. The aim of this study was to investigate the hemodynamic response patterns of patients with chronic insomnia disorder (CID) using the noninvasive and low-cost functional neuroimaging technique of multichannel nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…Yet, various neuroimaging studies on brain areas associated with affective cognition suggest impairments in patients with insomnia (e.g. atrophic hippocampal substructures, see [28]; dysfunctional prefrontal activity, see [29]).…”
Section: Neuroimaging Studies On the Amygdalamentioning
confidence: 99%
“…Yet, various neuroimaging studies on brain areas associated with affective cognition suggest impairments in patients with insomnia (e.g. atrophic hippocampal substructures, see [28]; dysfunctional prefrontal activity, see [29]).…”
Section: Neuroimaging Studies On the Amygdalamentioning
confidence: 99%
“…In a previous study, prefrontal cortical activation during VFT, assessed using fNIRS, was found to be reduced in chronic insomnia disorder. [ 30 ] The purpose of this study is to investigate the mechanism of action of YKSCH in patients with PD exhibiting sleep disorder, by confirming the hemodynamic changes in the frontal lobe caused by the administration of YKSCH.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] Hemodynamic responses, measured using fNIRS, during a VFT showed hypoactivation in the PFC of patients with chronic insomnia. [ 30 ] Therefore, our intention is to determine whether the concentrations of oxygenated hemoglobin in the PFC of patients with PD exhibiting sleep disorder is increased by YKSCH administration, using fNIRS during VFT. The test will be performed at baseline (visit 1) and after treatment (visit 4) in both groups.…”
Section: Methods and Designmentioning
confidence: 99%
“…[3941] Moreover, several studies have reported that this neural circuitry maybe sensitive to insomnia. [19,4245] Previous studies have shown impaired decision-making ability in the IGT in participants with sleep deprivation, as evidenced by their increased number of choices from disadvantageous decks. [46,47] A recent study from Seeley et al [48] suggested that sleep improves strategy-decision learning ability in the IGT; these results provide new insights into the relationship between sleep and IGT learning.…”
Section: Introductionmentioning
confidence: 99%
“…[46,50] Previous studies have also confirmed functional abnormalities in the prefrontal cortex of patients with PI. [38,45] These functional abnormalities may underlie the significant cognitive deficits associated with PI, which may include deficits in emotional memory and decision-making. However, whether PI shows analogous outcomes in emotional memory and decision-making, similar to sleep deprivation, remains unclear.…”
Section: Introductionmentioning
confidence: 99%